1979
DOI: 10.1111/j.1365-2125.1979.tb01025.x
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of salivary elimination of cyclophosphamide in man.

Abstract: 1 The concentrations of cyclophosphamide in plasma and saliva were determined in seven patients following administration of single doses of cyclophosphamide during chemotherapy for lymphoma. 2 The saliva/plasma ratio was 0.77 +/‐ 0.24 (s.d.) and showed no time‐ dependence being rapidly established following intravenous and oral administration. 3 The T 1/2 of cyclophosphamide (8.38 +/‐ 2.25 h) determined from salivary measurements was not significantly different from that in plasma (8.24 +/‐ 2.60 h). It was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

1981
1981
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 11 publications
1
3
1
Order By: Relevance
“…It is only recently that more interest has been placed on the pharmacokinetics of CP in high-dose therapy. 13,14 While the ␤-phase half-life (t 1/2␤ ) of CP obtained in this study is consistent with values reported previously, [15][16][17][18][19] the value of the ␤-phase volume of distribution (V t ) in this study was somewhat larger than those previously reported for the volume of distribution in humans, 20 which resulted in a markedly larger total clearance (CL) of CP as compared to that reported by other investigators. 16,19,21 It should be noted that when a similarly higher dose of CP was used, the volume of distribution at steady state (V ss ) (ie, 30.20 l) 12 was somewhat close to the value of V ss calculated in this study (ie 39.23 l).…”
Section: Tablesupporting
confidence: 57%
“…It is only recently that more interest has been placed on the pharmacokinetics of CP in high-dose therapy. 13,14 While the ␤-phase half-life (t 1/2␤ ) of CP obtained in this study is consistent with values reported previously, [15][16][17][18][19] the value of the ␤-phase volume of distribution (V t ) in this study was somewhat larger than those previously reported for the volume of distribution in humans, 20 which resulted in a markedly larger total clearance (CL) of CP as compared to that reported by other investigators. 16,19,21 It should be noted that when a similarly higher dose of CP was used, the volume of distribution at steady state (V ss ) (ie, 30.20 l) 12 was somewhat close to the value of V ss calculated in this study (ie 39.23 l).…”
Section: Tablesupporting
confidence: 57%
“…CPA in saliva was 13.6-79.0 (33.1 ± 13.2) mg/mL immediately after the chemotherapy, and then exponentially decreased with the passage of time (half-life of 6.62 ± 1.24 h, elimination rate constant of 0.171) (Figure 1). These values were slightly lower than that determined from saliva in male patients undergoing chemotherapy (half-life of 8.38 ± 2.25 h, elimination rate constant of 0.275) [8]. These results suggest that there are no sex differences in the elimination of CPA.…”
Section: Change In Salivary Cpacontrasting
confidence: 52%
“…including CPA) and had Performance Status (PS)of 0 or 1 (irrespective of age) [8]. The patients were asked to keep saliva for 3 days after outpatient chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been made to investigate, if saliva could be used as a noninvasive method for monitoring therapeutic drug concentrations (Danhof & Breimer, 1978). Concerning cytotoxic drugs such studies have been few including only a small number of patients (Juma et al, 1979;Patterson et al, 1981;Ritschel et al, 1981;Slavik et al, 1983;Steele et al, 1979). In the two hitherto published reports on MTX excretion in saliva there has been no general agreement as to the correlation between serum MTX and saliva Correspondence: Dr H. Schr0der, Department of Pediatrics, Aarhus Kommunehospital, DK 8000 Aarhus C, Denmark MTX concentrations (Patterson et al, 1981;Steele et al, 1979).…”
Section: Introductionmentioning
confidence: 99%